Report on Candidates' work in the Secondary Education Certificate Technical Proficiency Examination June 1990: Electrical Technology - Caribbean Examinations Council (CXC, 1990)
This report contains general and detailed comments on the performance of candidates in the June 1990 Caribbean Secondary Education Certificate (CSEC) technical proficiency examinations in Electrical Technology.
Keywords: CXC CSEC examinations